2016
DOI: 10.1007/s00265-015-2056-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of extra-pair paternity in a waterbird colony: separating the effects of nesting density and nest site location

Abstract: Centres of avian colonies are usually associated with reduced predation risk and, thus, attract individuals of high quality, while poor-quality individuals are relegated to peripheral zones. Assuming that the incidence of extra-pair paternity (EPP) is dependent on individual quality, we could expect lower incidence of extra-pair offspring in the central parts of colonies. On the other hand, central pairs often nest in higher densities, which might increase EPP rate. To test these hypotheses, we sampled 124 gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 72 publications
(75 reference statements)
1
2
0
Order By: Relevance
“…Similar variation has been recorded in great cormorants ( Phalacrocorax carbo sinensis ), where Minias et al (2016) found higher rates of extrapair paternity in the periphery than in the centre of a nesting colony. This pattern was not explained by density but by variation in mate quality, as indicated by nest site location.…”
Section: Discussionsupporting
confidence: 78%
“…Similar variation has been recorded in great cormorants ( Phalacrocorax carbo sinensis ), where Minias et al (2016) found higher rates of extrapair paternity in the periphery than in the centre of a nesting colony. This pattern was not explained by density but by variation in mate quality, as indicated by nest site location.…”
Section: Discussionsupporting
confidence: 78%
“…In other species of bird, females may solicit extra pair copulations to increase fertility and therefore reproductive output [21], however no documented evidence currently exists of female Greater Flamingos (wild or captive) actively seeking copulations outside of their breeding pair [14]. The behaviour documented in this occurrence indicates that this female flamingo had not initiated and was not interested in the advances of the male bird.…”
Section: Discussionmentioning
confidence: 98%
“…However, this avian group poses another challenge for this type of approach: attending adults are not easily captured at nests and genetic samples of complete families are therefore not available for conducting conventional parentage analyses [ 10 , 11 ]. Thus, so far, most inferences on the reproductive behavior of adults in wild waterbirds have been made mainly applying a methodological approach based on DNA-based kinship classification of nestling-pairs within nests, in the absence of parental genetic information [ 2 , 11 16 ]. However, there is ample agreement that greater statistical power is achieved in kinship analyses when more family members are sampled [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%